PERUBAHAN NET PROFIT MARGIN DAN DAMPAKNYA TERHADAP HARGA SAHAM: TINJAUAN PADA INDUSTRI MAKANAN DAN MINUMAN - Renil Septiano; Laynita Sari (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
The objective of this research is to examine the financial performance of energy companies listed on the Indonesia Stock Exchange (IDX) and how their stock prices have changed from 2018 to 2022. Academics are keen on understanding the factors influencing the stock prices of energy businesses due to recent market volatility in this sector. Seven companies listed on the IDX during the specified period are included in the sample, covering the entire population of these companies. Data were collected from the financial reports of these companies and analyzed using EViews software. The analysis found no statistically significant relationship between current ratio, debt equity ratio, net profit margin, and the stock prices of energy sector companies on the IDX during the study period. These results offer valuable insights for stakeholders, including investors and energy sector managers, in evaluating factors influencing stock prices and considering the potential impact of other factors in assessing the market valuation of energy companies. Further research is needed to explore other variables that may affect stock valuation in the energy sector and enhance understanding of the dynamics of the stock market in this sector